2018
DOI: 10.1097/corr.0000000000000419
|View full text |Cite
|
Sign up to set email alerts
|

What Are the MCIDs for PROMIS, NDI, and ODI Instruments Among Patients With Spinal Conditions?

Abstract: Level I, diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
135
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 51 publications
3
135
3
Order By: Relevance
“…To understand the clinical relevance of our findings, the differences in mean PROMIS scores by provider type can be compared to minimal clinically important differences (MCIDs) for PROMIS measures. Previously published PROMIS MCIDs for musculoskeletal patients with various diagnoses have ranged from 1.9 to 4.2 for Physical Function, 2.4 to 5.5 for Pain Interference, 2.3 to 3.4 for Anxiety, and 2.0 to 5.3 for Depression . Our results are within range of these values, which suggests the variation in PROMIS scores by provider type is likely clinically meaningful.…”
Section: Discussionsupporting
confidence: 72%
“…To understand the clinical relevance of our findings, the differences in mean PROMIS scores by provider type can be compared to minimal clinically important differences (MCIDs) for PROMIS measures. Previously published PROMIS MCIDs for musculoskeletal patients with various diagnoses have ranged from 1.9 to 4.2 for Physical Function, 2.4 to 5.5 for Pain Interference, 2.3 to 3.4 for Anxiety, and 2.0 to 5.3 for Depression . Our results are within range of these values, which suggests the variation in PROMIS scores by provider type is likely clinically meaningful.…”
Section: Discussionsupporting
confidence: 72%
“…Reporting PROM data based on CSO thresholds helps to build a more practical and patient-centered interpretation of PRO scores. [28][29][30][31] Hung et al 32 calculated the MCID for the PROMIS PF CAT using both distribution-and anchor-based methods in patients with spine conditions and found a median MCID of 8. SCB, introduced by Glassman et al 16 as an outcome measurement in spine orthopaedics, has remained largely unexplored in the lower-extremity sports medicine literature.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lack of standardization surrounding MCID calculation, overall reporting and desirability have increased in recent years. 6,8,16 The authors recognize that the PSI anchor, dichotomized by response, was not a validated assessment of clinical improvement; however, the methodology was consistent with several existing studies using similar subjective anchors. 9,15 Copay et al 9 found that a satisfaction-with-results scale was better associated with PROM change scores compared to the health transition item found on the Short Form of the Medical Outcomes Study (SF-36).…”
Section: Discussionmentioning
confidence: 69%
“…9 When compared to previously defined MCID thresholds in patients with low back pain, this study's results suggest that a MCID may not necessarily be considered a static value when applied to PROMs. 16 The expanding compilation of proposed values lends itself to the use of MCID ranges for different purposes. For instance, providers may tailor the use of MCID with respect to treatment risk.…”
Section: Discussionmentioning
confidence: 99%